Drainage Efficiency and Geometric Nuances of Tidal Channel Network Mediate Spartina alterniflora Landward Invasion in Marsh-Channel System - Zheng, Shaoyan; Shao, Dongdong; Gao, Weilun; Nardin, William; Ning, Zhonghua; Liu, Zezheng; Cui, Baoshan; Sun, Tao (Frontiers in Marine Science, 2022)
As an aggressive invasive salt marsh plant, Spartina alterniflora has been found to invade along tidal channel networks and threaten native salt marsh ecosystems. Previous studies have established patterning correlations between S. alterniflora invasion and tidal channel functions (drainage efficiency). However, a systematic analysis of S. alterniflora invasion in relation to functional and geometric features of tidal channel networks is still lacking. In this study, we extracted tidal channel networks from remote sensing images of the Yellow River Delta, China, and performed numerical experiments to examine S. alterniflora invasion patterns with tidal channel networks with varying drainage efficiency and geometric nuances. An existing vegetation dynamics model was adapted to incorporate hydrochorous seed dispersal and salinity buffer zone as the primary mechanisms of tidal channels to facilitate vegetation colonization and was further coupled with Delft3D. We analyzed the correlation of the simulated S. alterniflora area with a comprehensive set of tidal channel functional and geometric metrics across different spatial scales. Our results confirmed that watersheds with higher drainage efficiency (larger tidal channel density (TCD) and geometric efficiency (GE), smaller overmarsh path length (OPL)) attained larger S. alterniflora area. Given a similar drainage efficiency, tidal channel networks with greater geometric mean bifurcation ratio enhanced S. alterniflora invasion. On a local scale, channel order dictated local drainage efficiency (spatially-varying TCDo) and further influenced S. alterniflora area. The observed patterns were further verified in principle by two real cases in the Yellow River Delta. Finally, in viewing the efficacy of all metrics tested and further considering their computational costs, we proposed a holistic metric framework consisting of global metrics including TCD and geometric mean bifurcation ratio and local metric including spatially-varying TCDo, to assess how tidal channel network mediates S. alterniflora invasion in particular and salt marsh vegetation expansion in general in marsh-channel systems.